PENGARUH PEMBIAYAAN BAGI HASIL, JUAL BELI, FDR, NPF TERHADAP PROFITABILITAS BANK SYARIAH - Inayatillah, Yulia; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to examine the influence of profit sharing financing to the profitability of Sharia Commercial Banks, sale and purchase financing to the profitability of Sharia Commercial Banks, Non Performing Financing (NPF) to the profitability of Sharia Commercial Banks, and Financing to Deposit Ratio (FDR) to the profitability of Sharia Commercial Bank.The population of this research is 12 Sharia Commercial Banks which are listed in Bank of Indonesia in 2011-2015 periods. The sample collection technique has been conducted by using purposive sampling method and 10 samples have been selected during 2011-2015 periods. The data applies secondary data in the form of quarterly financial statement from each Sharia Commercial Bank. The data analysis method of this research has been carried out by using multiple linear regressions. The result of this research shows that sale and purchase financing give positive influence to the profitability, profit sharing financing does not give any influence to the profitability, Non Performing Financing (NPF) give negative influence to the profitability, and Financing to Deposit Ratio (FDR) give positive influence to the profitability.Keywords: Profitability, sale and purchase financing, profit sharing financing, Non Performing Financing (NPF), Financing to Deposit Ratio (FDR)